2021
DOI: 10.3389/fcell.2021.756483
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of N6-Methyladenosine RNA Methylation Regulators Expression Identify Distinct Molecular Subtypes of Myocardial Infarction

Abstract: Background: Myocardial infarction (MI) is one of the leading threats to human health. N6-methyladenosine (m6A) modification, as a pivotal regulator of messenger RNA stability, protein expression, and cellular processes, exhibits important roles in the development of cardiac remodeling and cardiomyocyte contractile function.Methods: The expression levels of m6A regulators were analyzed using the GSE5406 database. We analyzed genome-wide association study data and single-cell sequencing data to confirm the funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…The calibration and DCA plots also showed the very good fit of the model. Similar to previous findings (18,28), the model showed that methylation was an important molecular change in the development of AMI. Under the model, the 5 most important genes were FTO, WTAP, YTHDC1, IGFBP3, and CBLL1.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The calibration and DCA plots also showed the very good fit of the model. Similar to previous findings (18,28), the model showed that methylation was an important molecular change in the development of AMI. Under the model, the 5 most important genes were FTO, WTAP, YTHDC1, IGFBP3, and CBLL1.…”
Section: Discussionsupporting
confidence: 87%
“…A previous study found that m6A methylation is widely involved in the development of various types of cardiovascular diseases and plays an important regulatory role in heart failure, myocardial hypertrophy, atherosclerosis, and ischemic cardiomyopathy (17). m6A modification, as a pivotal regulator of messenger RNA stability, protein expression, and cellular processes, exhibits important roles in the development of cardiac remodeling and cardiomyocyte contractile function (18). AMI leads to cell death, which promotes the immune inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…Other reports also demonstrated that cytoplasmic YTHDF3 promotes mRNA translation in synergy with YTHDF1 , meanwhile affecting methylated mRNA decay mediated through YTHDF2 and serves as an initiation factor of protein synthesis from circRNAs in human cells ( 44 46 ). For the potential roles of YTHDF3 in cardiovascular diseases, genome-wide association studies (GWAS) showed that SNP rs4739066 on YTHDF3 is significantly associated with myocardial infarction (MI) and Shi et al also found that YTHDF3 is dramatically differentially expressed in MI tissues compared with normal controls ( 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this manner, studies have shown that the Ckap4 marker was specifically induced in activated fibroblasts ( 34 ), and exclusive Ddah1 expression in myofibroblasts during MI healing ( 22 ) which may indicate novel activated fibroblast markers. Recently, Shi et al ( 56 ) found the expression levels of FTO (fat mass and obesity-associated protein), YTHDF3 (YTH domain-containing protein 3), ZC3H13 (a zinc finger protein), and WTAP (Wilms' tumor 1-associating protein) were significantly different in myocardial infarction tissues, demonstrating the key role of N6-methyladenosine (m6A) regulator in myocardial infarction. WTAP was significantly reduced in the MI group, and maintaining the normal expression of WTAP may be a preventive or ameliorative means for the treatment of MI.…”
Section: Fibroblast Activationmentioning
confidence: 99%